Investigation of potential genotoxic activity using the SOS Chromotest for real paracetamol wastewater and the wastewater treated by the Fenton process - Kocak, Emel (BIOMED CENTRAL LTD, 2015)
Background: The potential genotoxic activity associated with high strength real paracetamol (PCT) wastewater (COD = 40,000 mg/L, TOC = 12,000 mg/L, BOD5 = 19,320 mg/L) from a large-scale drug-producing plant in the Marmara Region, was investigated in pre- and post-treated wastewater by the Fenton process (COD = 2,920 mg/L, TOC = 880 mg/L; BOD5 = 870 mg/L). Methods: The SOS Chromotest, which is based on Escherichia coli PQ37 activities, was used for the assessment of genotoxicity. The corrected induction factors (CIF) values used as quantitative measurements of the genotoxic activity were obtained from a total of four different dilutions (100, 50, 6.25, and 0.078 % v/v.) for two samples, in triplicate, to detect potentially genotoxic activities with the SOS Chromotest. Results: The results of the SOS Chromotest demonstrated CIFmax value of 1.24, indicating that the PCT effluent (non-treated) is genotoxic. The results of the SOS Chromotest showed an CIFmax value of 1.72, indicating that the wastewater treated by Fenton process is genotoxic. Conclusions: The findings of this study clearly reveal that the PCT wastewater (non-treated) samples have a potentially hazardous impact on the aquatic environment before treatment, and in the wastewater that was treated by the Fenton process, genotoxicity generally increased.
Keywords: Induction factor; Escherichia coli PQ37; Fenton process; Real paracetamol wastewater; SOS Chromotest; ADVANCED OXIDATION PROCESSES; FLUCTUATION TEST; MUTAGENICITY; DEGRADATION; ENVIRONMENT; INDUSTRIAL; EFFLUENTS; CANCERS; ESTUARY; SYSTEMS; Engineering; Environmental Sciences & Ecology